EVALUASI PROGRAM SEKOLAH SEHAT DI SEKOLAH DASAR NEGERI - Zubaidah, Siti; Ismanto, Bambang; Sulasmono, Bambang Suteng (Universitas Kristen Satya Wacana, 2017)
The aimed of this study was to evaluate the context, input, process, product of Healthy School program in Public School Kutowinangun 04 Salatiga (SD Negeri Kutowinangun 04 Salatiga). This study was evaluative research using CIPP model. The technique of collecting data using interviews, observation and documentation. Some of the steps being taken in the analysis of the data included: data collection, data reduction, data display and verification. Validation of data using triangulation techniques and resources. The results showed: (1) from the aspects of Context, the Healthy School program was the policy of the central government to improve the quality of education through the improvement of students health, in addition to the schools needs, especially the students in Public School Kutowinangun 04 SalatigaÂ were still low level of health, (2) from the aspect of Input, design program proved to be able to answer the need for the program to address the low level of students health, and supported by human resources, facilities and infrastructure, adequate cost, 3) from the aspect of Process, Healthy School Program has been run in accordance with program planned but on its implementation there were obstacles where schools have limited funds and inadequate infrastructure, and (4) from the aspect of Product, all targets to be achieved in program planned has been reached so that impacted the improvement of the quality of education in Public School Kutowinangun 04 Salatiga and therefore eligible to continue in the next period with several aspects improvements.